Definition S.CR.1Let X,Y be sets. We define that |X|=|Y| if and only if there exist a function f:X->Y and f is 1-1 and "onto".Remark:Notice that we don't define the operator |.|. We define the predicate P(X,Y)="|X|=|Y|".Definition S.CR.2Let X,Y be sets. We define that |X|<=|Y| if and only if there exist a function f:X->Y and f is 1-1.Lemma S.CR.3If X,Y are sets, X c Y and |Y|<=|X| then |X|=|Y|.ProofBy assumption we have f:Y-1-1->X. Let F[A] = X\f(Y\A) for all A c X. Notice that By Theorem S.IS.4 if A c B then F[A] c F[B]. Let W = {A:-P(X)|A c F(A)}. Let E = u(W). We will show that E:-W. We have to show that E c X\f(Y\E). Take any e:-E. We have an A:-W such that e:-A. Since A:-W, A c F[A]. And since A:-W, A c E. Then F[A] c F[E]. Thus e:-F[E]. We have showed that E:-W. We will show that F[E] = E. Since E c F[E], F[E] c F[F[E]]. Hence F[E]:-W. So F[E] c E. Thus E = F[E]. We have E = X\f(Y\E). So X\E = f(Y\E). Let g:Y->X such that / x for x:-E, g(x) = { \ f(x) for x:-Y\E. We will show that g:Y-1-1-onto->X. (1-1) Take any x1,x2:-Y such that x1 != x2. If x1:-E and x2:-Y\E then g(x1) = x1 and g(x2):-f(Y\E)=X\E. And then g(x1) != g(x2). If x1,x2:-E then x1=g(x1)!=g(x2)=x2. If x1,x2:-Y\E then f(x1)=g(x1)!=g(x2)=f(x2) because f is 1-1. Thus g:Y-1-1->X. We have shown (1-1). (onto) g(Y) = g((Y\E) u E) = g(Y\E) u g(E) = f(Y\E) u E = X\E u E = X. We have shown (onto). We have shown that g:X-1-1-onto->Y. Thus |X|=|Y|.Theorem S.CR.4If X,Y are sets then the statements below hold. (1) |X|=|X|, (2) |X|=|Y| <=> |Y|=|X|, (3) |X|=|Y| and |Y|=|Z| => |X|=|Z|, (4) X c Y => |X|<=|Y|, (5) |X|=|Y| and |Y|<=|Z| => |X|<=|Z|, (6) |X|=|Y| and |Z|<=|Y| => |Z|<=|X|, (7) |X|<=|X|, (8) |X|<=|Y| and |Y|<=|Z| => |X|<=|Z|, (9) |X|<=|Y| and |Y|<=|X| => |X|=|Y|.Proof(1) Let f:X->X such that /\(x:-X) f(x)=x. Thus f:X-1-1-onto->Y. (2) If f:X-1-1-onto->Y then f^(-1):Y-1-1-onto->X. (3) If f:X-1-1-onto->Y and g:Y-1-1-onto->Z then gof:X-1-1-onto->Z. (4) Let f:X->Y such that /\(x:-X) f(x)=x. Thus f:X-1-1->Y. (5) If f:X-1-1-onto->Y and g:Y-1-1->Z then gof:X-1-1->Z. (6) If f:X-1-1-onto->Y and g:Z-1-1->Y. Then (f^(-1))o(g):Z-1-1->X. (7) Let f:X->X such that /\(x:-X) f(x)=x. Thus f:X-1-1->Y. (8) If f:X-1-1->Y and g:Y-1-1->Z then gof:X-1-1->Z. (9) We have f:X-1-1->Y and g:Y-1-1-X. Notice that f:X-1-1-onto->f(X). So |f(X)|=|X|. Since |Y|<=|X|, |Y|<=|f(X)| by (5). Since f(X) c Y, |Y|=|f(X)| by Lemma S.CR.3. By (3) |Y|=|X|.AC.Theorem S.CR.5If X,Y are sets then |X|<=|Y| or |Y|<=|X|.ProofAssume that the Axiom of Choice holds. We will use Zorn's Lemma. (*)Assume that !(|Y|<=|X|). Let P = {f:-P(XxY)|f is 1-1}. Notice that (P,c) is a partially ordered set. Take any chain L c P. By Theorem S.C.14 u(L) is a function. We will show that u(L):-P. Let g = u(L). Take any x1,x2:-X such that g(x1) = g(x2). So there exists y:-Y such that (x1,y):-g and (x2,y):-g. We have h1,h2:-L such that (x1,y):-h1 and (x2,y):-h2. Since L is a chain, (h1 u h2) = h1 or (h1 u h2) = h2. Hence (h1 u h2):-L and (h1 u h2)(x1) = (h1 u h2)(x2). Since (h1 u h2):-P, x1 = x2. Thus u(L) is 1-1. We have shown that u(L):-P. It is obvious that /\(g:-L) g c u(L). Recall that L was arbitralily chosen. Then for every chain in P there exists an upper bound in P. Now by Zorn's Lemma we have an f:-P such that /\(g:-P) f c g => f=g. By assumption (*) f is not "onto". If it was it would be f^(-1):Y-1-1->X and then |Y|<=|X|. We will show that f:X-1-1->Y. It is enough to show that /\(x:-X)\/(y:-Y) (x,y):-f. Assume to the contrary that we have x0:-X such that for every y:-Y !( (x,y):-f ). Since f is not "onto", we have y0:-Y such that /\(x:-X) !( (x,y0):-f ). Let g = f u {(x0,y0)}. Notice that g is a function and g is 1-1. Then g:-P and f c g. So g = f. Contradiction. So /\(x:-X)\/(y:-Y) (x,y):-f. Thus f:X-1-1->Y. We assumed that !( |Y|<=|X| ) and and we have shown that |X|<=|Y|. The proof is complete.Definition S.CR.6Let X,Y be sets. We define that |X|<|Y| if and only if |X|<=|Y| and !(|X|=|Y|).Theorem S.CR.7If X is a set then |X|<|P(X)|.ProofAssume to the contrary that we have f:X-onto->P(X). Let A = {x:-X | !(x:-f(x))}. Since f is onto, we have a:-X such that f(a)=A. If a:-A then a:-f(a) and then !(a:-A). If !(a:-A) then !(a:-f(a)) and then a:-A. Contradiction. Thus !(|X|=|P(X)|). Let g:X->P(X) such that /\(x:-X) g(x)={x}. So g:X-1-1->P(X). Thus |X|<=|P(X)|. We have proved that |X|<|P(X)|.